THE ROLE OF AUTHENTIC WRITING TASKS IN LANGUAGE LEARNING (Лучшие интеллектуальные исследования, 2025)
Abstract. In the context of language learning, writing serves not only as a means of communication but also as a tool for reinforcing grammatical structures, vocabulary usage, and critical thinking. Recent pedagogical shifts emphasize the importance of authentic writing tasks—activities that mirror real-world communicative purposes—in promoting learner engagement and meaningful language use. Unlike traditional exercises focused on mechanical accuracy, authentic writing tasks challenge learners to express their thoughts in contextually appropriate and personally relevant ways. These tasks include composing emails, blog posts, reviews, social media updates, and formal letters—genres commonly encountered in everyday life. By incorporating such tasks into the curriculum, language teachers can help students develop not only linguistic accuracy but also communicative competence and pragmatic awareness. This paper explores how authentic writing tasks contribute to improved language proficiency and learner motivation across various educational settings.